A Systematic Literature Review on the Investigation and Application of Vegetable Fibers in Textiles/Apparel and Future Research Agenda - Shuyang Li; Chris K. Y. Lo; Li Li (Journal of Natural Fibers)
Vegetable fibers have attracted increasing attention from researchers and manufacturers in the textile and apparel industry for their renewable, biodegradable, and eco-friendly features. However, due to the scattered nature and rapid development, a review that adopts a holistic perspective and analyzes the knowledge evolution structure of the vegetable fiber domain could hardly be found. This paper systematically reviewed the research progress and frontiers of the vegetable fiber domain over the past 25 years, with bibliometric analysis and knowledge mapping (by VOSviewer) of the 179 relevant articles retrieved from the Web of Science. A rapid increase in publications and citations was observed in the recent 5 years. India, China, and Turkey, with competitive textile industries and diverse agricultural sectors, have been active in vegetable fiber research. According to the clustering result of co-citation analysis, fiber-reinforced composites, vegetable fibers with sound/thermal insulation, and natural colorants were the main research topics with the most cited articles. “Knitting,” “insulation,” “Indian pineapple leaf,” and “color strength” were identified as the emerging research hotspots based on the keyword co-occurrence network. Future studies are expected to improve efficiency and automation, meanwhile decreasing the cost and environmental impact throughout the whole process chain of vegetable fibers.